1989
DOI: 10.1007/bf00253630
|View full text |Cite
|
Sign up to set email alerts
|

Synchronized neuronal activities in neocortical explant cultures

Abstract: Intracellular recordings revealed that in neocortical explant cultures prepared on the day of birth and examined 3-6 weeks later, neurons mature and establish complex synaptic relationships that lead to spontaneous and triggered synchronous discharge. The spontaneous synchronous activity took several forms, including periodic generation of epileptiform depolarizing waves, prolonged periods of seizure-like discharge, and periodic, intense barrages of IPSPs. Synchronous depolarizations were associated with a mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
6
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 36 publications
4
6
0
Order By: Relevance
“…The nLFP peaks were indicative of population spikes (Jimbo and Robinson, 2000; Bédard et al, 2004) and occurred in bursts of approximately synchronous activity with quiescent intervals spanning several seconds (Fig. 1 B ), consistent with previous studies (Crain, 1966; Calvet, 1974; Gutnick et al, 1989; Maeda et al, 1995; Kamioka et al, 1996; Plenz and Aertsen, 1996; Corner et al, 2002; Eytan and Marom, 2006). The timing of the detected nLFP peaks is sufficient to reveal important spatiotemporal patterns of the activities obeying power scaling law, so-called neuronal avalanches (Beggs and Plenz, 2003, 2004; Stewart and Plenz, 2006; Gireesh and Plenz, 2008).…”
Section: Resultssupporting
confidence: 90%
“…The nLFP peaks were indicative of population spikes (Jimbo and Robinson, 2000; Bédard et al, 2004) and occurred in bursts of approximately synchronous activity with quiescent intervals spanning several seconds (Fig. 1 B ), consistent with previous studies (Crain, 1966; Calvet, 1974; Gutnick et al, 1989; Maeda et al, 1995; Kamioka et al, 1996; Plenz and Aertsen, 1996; Corner et al, 2002; Eytan and Marom, 2006). The timing of the detected nLFP peaks is sufficient to reveal important spatiotemporal patterns of the activities obeying power scaling law, so-called neuronal avalanches (Beggs and Plenz, 2003, 2004; Stewart and Plenz, 2006; Gireesh and Plenz, 2008).…”
Section: Resultssupporting
confidence: 90%
“…1 B), in agreement with previous reports of synchronized bursting in dissociated and cortical slice cultures (Crain, 1966;Calvet, 1974: Gutnick et al, 1989Maeda et al, 1995;Gopal and Gross, 1996;Kamioka et al, 1996;Plenz and Aertsen, 1996b;Plenz and Kitai, 1996). Our recent analysis revealed that these epochs are composed of neuronal avalanches, successive but distinct periods of neuronal activity with inherently complex spatiotemporal structure (Fig.…”
Section: General Description Of Cultures and Spontaneous Activitysupporting
confidence: 90%
“…Average multiunit firing rates were variable between cultures (median 5.1 Hz, interquartile range 1.4–8.6 Hz), in all likelihood due to the variable number of neurons recorded from per electrode. Overall, activity patterns combined features typical of networks hyperexcited by nominally zero extracellular magnesium (Gutnick et al, 1989; Kawaguchi, 2001) and features reported in previous studies on rat neocortical slice cultures in less activity-fostering conditions (Plenz and Kitai, 1996; Klostermann and Wahle, 1999; Hentschke et al, 2005; Johnson and Buonomano, 2007; Czarnecki et al, 2012). …”
Section: Resultssupporting
confidence: 58%
“…In order to assess the contribution of GABA A versus GABA B receptors to the inhibitory effects of NO-711, we performed experiments in which blockers of either receptor type were applied prior to NO-711. GABA A receptor blockade by 100 μM bicuculline transformed activity into a regular pattern of stereotyped bursts characterized by intense firing activity, strong oscillatory (~10 Hz) components and prolonged silent periods between bursts, typical of disinhibited cortical networks (Gutnick et al, 1989; Castro-Alamancos et al, 2007; Sanchez-Vives et al, 2010; Figures 4A,C ). By contrast, GABA B receptor blockade by CGP 55845 (5 or 10 μM) altered activity in a moderate and selective manner, primarily by prolonging bursts ( Figures 4B,D ).…”
Section: Resultsmentioning
confidence: 99%